The Education Funding Management of Dayah Khairuddaraini Kabupaten Pidie - Azhari Azhari; Cut Zahri Harun; Khairuddin Khairuddin (Proceedings of AICS - Social Sciences, 2019)
The purpose of this study is to get an overview of Educational Funding Management of Dayah Khairuddaraini Gampong Leun Tanjong Padang Tiji in Pidie District that consist of the source of Funding and financial accountability of Dayah Khairuddaraini institution. This research was conducted considering financial management is one of the activities in managing an educational institution that cannot be separated from the study of education management. Interview, observation, and documents analysis were used to collect the data of this qualitative research to answer both of the research questions. The leader of Dayah, secretary, treasurer and the teacher of the Dayah are used to be the subject of this study. The data analyzed and described qualitatively after collecting and sorting it based on each research questions. The research showed that: 1) The source of funding of Dayah Khairuddaraini institution got from some resourses: Acehnese government, Waqf, Zakat, Sedeqah or charity, donation from the students’ parent, and The contribution of Banda Aceh-Medan Road user. 2) The secretary and Treasurer made financial accountability regularly to be presented to the leader of that institution and also as the supervisor of Dayah financial accountability. Besides that, leader of this Dayah also makes the report of funding by himself, especially the source of funding from the highway user of Banda Aceh-Medan.